Babilangan in the Marriage Traditions of the Banjar Community in South Kalimantan: A Legal Pluralism Perspective - Helim, Abdul; Ilmi, Muhammad; Ahmad, Sabarudin; Vennovary Benevolent, Wafid Syuja’ (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2025)
Babilangan is an effort by the people of South Kalimantan to find out a person's compatibility with their potential partner, before getting married. However, in North Hulu Sungai Regency, Babilangan has been responded to with prolonged pros and cons. The main problem studied in this research is the practice of babilangan in pre-wedding Banjar communities in South Kalimantan. This research uses empirical legal methods with a legal pluralism approach. Data was collected by means of in-depth interviews and literature study. The informants interviewed were religious leaders, traditional and community leaders, while the literature study referred to journal articles, books and supporting references. This research concludes that although there are pros and cons to Babilangan, they are resolved using al-jam'u wa at-taufiq and legal pluralism. The way Babilangan works and the dialogue with other scientific theories means that Babilangan's function today is relevant as research through inner channels into the profile of a potential household partner. If we refer to the theory of legal pluralism, then babilangan is in accordance with Islamic law because it has mashlahat value and no legal violations have been found, in fact, babilangan can be categorized as 'urf sahih, namely a custom that is acceptable by the Islamic law. Its function is as part of a prediction regarding the profile of a prospective partner before the marriage takes place, which can still be used today. Meanwhile, in customary law, the Babilangan tradition is a cultural practice with the aim of a happy marriage and physical and spiritual prosperity.